Ketamine administration in idiopathic epileptic and healthy control dogs: Can we detect differences in brain metabolite response with spectroscopy? - Wieser, Manuela; Beckmann, Katrin Melanie; Kutter, Annette P. N.; Mauri, Nico; Richter, Henning; Zölch, Niklaus; Bektas, Rima Nadine (Frontiers in Veterinary Science, 2023)
Introduction In recent years ketamine has increasingly become the focus of multimodal emergency management for epileptic seizures. However, little is known about the effect of ketamine on brain metabolites in epileptic patients. Magnetic resonance spectroscopy (MRS) is a non-invasive technique to estimate brain metabolites in vivo. Our aim was to measure the effect of ketamine on thalamic metabolites in idiopathic epileptic (IE) dogs using 3 Tesla MRS. We hypothesized that ketamine would increase the glutamine—glutamate (GLX)/creatine ratio in epileptic dogs with and without antiseizure drug treatment, but not in control dogs. Furthermore, we hypothesized that no different responses after ketamine administration in other measured brain metabolite ratios between the different groups would be detected. Methods In this controlled prospective experimental trial IE dogs with or without antiseizure drug treatment and healthy client-owned relatives of the breeds Border Collie and Greater Swiss Mountain Dog, were included. After sedation with butorphanol, induction with propofol and maintenance with sevoflurane in oxygen and air, a single voxel MRS at the level of the thalamus was performed before and 2 min after intravenous administration of 1 mg/kg ketamine. An automated data processing spectral fitting linear combination model algorithm was used to estimate all commonly measured metabolite ratios. A mixed ANOVA with the independent variables ketamine administration and group allocation was performed for all measured metabolites. A p < 0.05 was considered statistically significant. Results Twelve healthy control dogs, 10 untreated IE and 12 treated IE dogs were included. No significant effects for GLX/creatine were found. However, increased glucose/creatine ratios were found (p < 0.001) with no effect of group allocation. Furthermore, increases in the GABA/creatine ratio were found in IEU dogs. Discussion MRS was able to detect changes in metabolite/creatine ratios after intravenous administration of 1 mg/kg ketamine in dogs and no evidence was found that excitatory effects are induced in the thalamus. Although it is beyond the scope of this study to investigate the antiseizure potential of ketamine in dogs, results of this research suggest that the effect of ketamine on the brain metabolites could be dependent on the concentrations of brain metabolites before administration.